Genetic variation in high light responses of Theobroma cacao L. accessions. Issue 6 (June 2021) - Lewis, Vernessa R.; Farrell, Aidan D.; Umaharan, Pathmanathan; Lennon, Adrian M.
Abstract: Cacao ( Theobroma cacao L.) is a shade-tolerant tree species, but in recent years it has increasingly been cultivated under full sun conditions in an orchard system where photoinhibition is likely. Here we investigate the extent of photoinhibition in 17 cacao accessions from a range of genetic groups, growing under high light conditions. The ability of the photosynthetic systems to respond to high light was assessed using chlorophyll fluorescence parameters (diurnal F v / F m and instantaneous light response curves), and differences in photosynthetic pigment content were compared using biochemical assays. Damage due to photoinhibition was assessed using electrolyte leakage, lipid peroxidation, and reactive oxygen species scavenging systems were compared using biochemical assays (for APX, CAT and SOD). There was significant variation between the 17 accessions for photosynthetic parameters, although in all cases the light saturation points were well below the midday light levels. Light acclimation of photosynthetic pigments was evident and variation in the total chlorophyll to total carotenoid ratio was significantly correlated with electrolyte leakage. Significant genetic variation was observed across the 17 accessions in the activities of CAT, APX and SOD. Across all accessions, photoprotection appeared to be restricted by the ability of leaves to generate SOD. Significant negative correlations were observed between SOD activity and both APX activity and electrolyte leakage, while significant positive correlations were observed between electrolyte leakage and both APX and CAT activity. Accessions with higher light saturation points, as well as high carotenoid and high SOD concentrations were able to tolerate the moderately high light, however, none of the accessions were clearly superior to the commonly grown Amelonado accession. The results imply that screening for SOD activity, total carotenoid content and light saturation point can aid in selection of genotypes with better tolerance to high light. Abstract : ascorbate peroxidase, photoinhibition, photosynthesis, reactive oxygen species, superoxide dismutase.